Pemanfaatan Teknologi Informasi Dan Komunikasi Sebagai Media Pembelajaran - Sodiq Anshori (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
Learning media is one means of channeling messages and learning information. Welldesigned learning media, greatly helps learners to digest and understand the subject matter.The development of information technology in the era of globalization and informationtoday, spur the development of learning media progressively advanced as well. Use ofInformation and Communication Technology (ICT) as a learning medium is already ademand. Although the design of ICT-based media requires special skills, it does not meanthe media is avoided and abandoned. ICT-based learning media can be internet, intranet,mobile phone, and CD Room / Flash Disk.Advances in Information Technology has encouraged many changes, including in thefield of education that gave birth to the concept of e-learning. With e-learning, theimplementation of learning becomes more effective and efficient. E-learning enableslearners to be active and creative. E-learning provides educators, educators andeducational managers with many benefits, including program flexibility and learningmaterials that can be made more interesting and memorable. The integration of informationtechnology in education will improve the quality of learning. The impact of follow-up withthe integration of information technology in education is to encourage the acceleration ofcomputer literacy in Indonesian society.Utilizing technology as a learning medium in the process of teaching and learning,can facilitate the way teachers in communicating and interacting with students both in theclassroom and outside the class. The need for technology in the realm of education is notnew, the use of technology to form a conducive and innovative learner . Utilization is provento play a big role in the smooth process of learning.